State-sponsored price transparency programs for ophthalmic services. Issue 4 (December 2022) - Lin, John C; Ghauri, Sophia Y; French, Dustin D; Scott, Ingrid U; Greenberg, Paul B
Abstract: Objectives: To characterize the information provided by state-sponsored price transparency programs and describe price variation for ophthalmic services. Methods: We searched for state-sponsored price transparency programs and reviewed all available information on ophthalmic services. Results: In total, 55% (6/11) of state-sponsored price transparency programs included ophthalmic services. Three provided nonfinancial value metrics, five provided prices by clinician organization, and none reported out-of-pocket costs, insurance costs, or prices by insurers for ophthalmic services. The median within-state price ratio was 3.65 (interquartile ratio [IQR]: 2.04–7.91). Mean prices for cataract surgery ranged from 2575 to 5097 and from 873 and 27, 801.66 for retinal detachment repair. Discussion: Most of the eleven state-sponsored price transparency programs included pricing information for ophthalmic services. No programs provided specific out-of-pocket costs, insurance costs, or prices by insurers for ophthalmic services. There was substantial variation in prices for all included ophthalmic services within and between states.